Public policies of sexual and reproductive health in Peru: the introduction of therapeutic abortion regulation into the government’s political agenda - Leiva Rioja, Zoila (2016)
The objective of the present article is to analyze the process of introducing the regulation of therapeutic abortion into the peruvian governmental agenda, identifying the factors that came together to generate such event, the period of study being between the years 2005 to 2014. The investigation corroborates that said event was possible due to the confluence of certain political and institutional factors on the national stages, the strategy of groups in favor (pro-choice) and against (pro-life) the regulation, and international influence.